Hepatitis C Virus as a Possible Helper Virus in Human Hepatitis Delta Virus Infection - Crobu, Maria Grazia; Ravanini, Paolo; Impaloni, Clotilde; Martello, Claudia; Bargiacchi, Olivia; Di Domenico, Christian; Faolotto, Giulia; Macaluso, Paola; Mercandino, Alessio; Riggi, Miriam; Quaglia, Vittorio; Andreoni, Stefano; et al. (Viruses, 2024)
Previous studies reported that the hepatitis C virus (HCV) could help disseminate the hepatitis D virus (HDV) in vivo through the unrelated hepatitis B virus (HBV), but with essentially inconclusive results. To try to shed light on this still-debated topic, 146 anti-HCV-positive subjects (of whom 91 HCV/HIV co-infected, and 43 with prior HCV eradication) were screened for anti-HDV antibodies (anti-HD), after careful selection for negativity to any serologic or virologic marker of current or past HBV infection. One single HCV/HIV co-infected patient (0.7%) tested highly positive for anti-HD, but with no positive HDV-RNA. Her husband, in turn, was a HCV/HIV co-infected subject with a previous contact with HBV. While conducting a thorough review of the relevant literature, the authors attempted to exhaustively describe the medical history of both the anti-HD-positive patient and her partner, believing it to be the key to dissecting the possible complex mechanisms of HDV transmission from one subject to another, and speculating that in the present case, it may have been HCV itself that behaved as an HDV helper virus. In conclusion, this preliminary research, while needing further validation in large prospective studies, provided some further evidence of a role of HCV in HDV dissemination in humans.